A 2D frequency-domain wave based method for dynamic analysis of orthotropic solids. (1st October 2020) - Sun, Linlin; Wei, Xing; Chu, Liu
Highlights: The wave based method with new wave functions in vector forms is proposed. The scaling factors are employed to normalize the proposed wave functions. The present method is well feasible for various orthotropic dynamic problems. The proposed method is accurate and efficient for a wide range of frequencies. Abstract: In this paper, a new version of the wave based method (WBM) is proposed for the dynamic analysis of orthotropic solids in the frequency domain. Different from the conventional WBM in general elastic dynamic problems, a set of new wave functions in vector forms are derived in the present WBM to effectively avoid decomposing the governing equations into Helmholtz equations. Particularly, scaling factors are introduced to improve the properties of the wave functions. With the new wave functions satisfying the governing equations, the present method not only inherits the advantages of the conventional WBM, but also eliminates its restrictions of the application to orthotropic dynamic problems. In comparison with the results of the finite element method (FEM), the efficiency, accuracy and convergence rate of the present method are verified by examples with different geometries, materials and boundary conditions.